The Development OF PQ4R-TPS Learning Strategies for Empowering Students' Scientific Attitudes and HOTS - Henny Setiawati (Indonesian Research Journal in Education |IRJE|, 2022)
Biology in secondary schools is still largely oriented to mastery of concepts and has not attempted to empower students' scientific attitudes and higher order thinking skills (HOTS). It has implications for the attitudes and cognitive abilities of students who tend to be low. The problems found in the learning process are related to the lack of application of students' scientific attitudes and HOTS. Teachers do not have learning tools that support the development of scientific attitudes and HOTS. The development of learning tools using constructive strategies is an effective alternative solution that can be used by teachers to overcome these problems. One of the constructive strategies that are considered appropriate to be developed is the PQ4R and TPS strategies. Therefore, this research aims to develop an oriented biology learning tool for empowering students' scientific attitudes and HOTS. Efforts to combine PQ4R and TPS strategies to maximize the potential of these two strategies. The strategy development method follows the Thiagarajan 4D learning design model. The results of this strategy development will be implemented into learning tools.